2020
DOI: 10.1038/s41598-020-74250-2
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 and BRCA2 genes mutations among high risk breast cancer patients in Jordan

Abstract: Familial breast cancer is estimated to account for 15–20% of all cases of breast cancer. Surveillance for familial breast cancer is well-established world-wide. However, this service does not exist in Jordan, due to the scarcity of information with regard to the genetic profiling of these patients, and therefore lack of recommendations for policy-makers. As such, patients with very strong family history of breast or ovarian cancers are not screened routinely; leading to preventable delay in diagnosis. Whole co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…The local cancer registry reports reveal that 20.5% of all BC cases in Jordan occur in women younger than 40 16 , in contrast with the reported 10.2% of BC cases occurring before the age of 45 in the United States 10 . These observations, along with the relatively high rate of BRCA1- and BRCA2- associated BC cases reported among Jordanian patients, can be considered as additional key factors that contribute to a genetically-enriched landscape for BC disease patterns, with potential for distinctive age-defined outcomes 17 , 18 . This study managed to identify the ways by which the Jordanian BC population both adhered to, or deviated from, the global trends of age-related differences in breast cancer presentation and treatment outcomes.…”
Section: Discussionmentioning
confidence: 94%
“…The local cancer registry reports reveal that 20.5% of all BC cases in Jordan occur in women younger than 40 16 , in contrast with the reported 10.2% of BC cases occurring before the age of 45 in the United States 10 . These observations, along with the relatively high rate of BRCA1- and BRCA2- associated BC cases reported among Jordanian patients, can be considered as additional key factors that contribute to a genetically-enriched landscape for BC disease patterns, with potential for distinctive age-defined outcomes 17 , 18 . This study managed to identify the ways by which the Jordanian BC population both adhered to, or deviated from, the global trends of age-related differences in breast cancer presentation and treatment outcomes.…”
Section: Discussionmentioning
confidence: 94%
“…Another common mutation BRCA1 c.3756_3759delGTCT has been detected in some populations, such as Thai [55], Polish [56], Belarusian [57], Italian [58], French-Canadian [59], and Czech populations [60]. BRCA1 c.4065_4068del has been detected in some populations [61][62][63]. Another study showed that c.4065_4068del is one of the three most common BRCA1 variants in Chinese ovarian cancer patients [47].…”
Section: Discussionmentioning
confidence: 99%
“… 4 In fact, only 5–10% of breast cancer cases are thought to have a genetic background, with BRCA1/2 germline mutations contributing to approximately 50% of these hereditary cases. 5 , 6 …”
Section: Introductionmentioning
confidence: 99%
“…4 In fact, only 5-10% of breast cancer cases are thought to have a genetic background, with BRCA1/2 germline mutations contributing to approximately 50% of these hereditary cases. 5,6 Breast cancer is a heterogenous disease owing to the existence of molecular and phenotypic variations within a patient's tumor (intra-tumoral heterogeneity) and between different patients' tumors (inter-tumoral heterogeneity). 7 Based on immunohistochemistry and gene expression profiling, breast cancer can be classified into different biological subtypes.…”
Section: Introductionmentioning
confidence: 99%